The Economic Analysis of Expectation Formation and the Rational Expectation Hypothesis - Islam, Aminul (Indian Journal of Finance, 2010)
The idea of "rational expectations" has had a profound impact in shaping the economic theory. More dramatically, it has shaken the foundation of macroeconomic theory and has been associated almost exclusively with the so called New Classical revolution in macroeconomics. This idea is revolutionary because it attempts to focus attention on the underpinnings of economics: individual behaviour. Essentially, it enhances the behavioral assumptions of the "rational economic man" made by the conventional economic theory. This enhancement is done by extending the notion of rationality to the learning process. How do people learn? How do they acquire and process information to make accurate decisions? How do they handle uncertainty? More generally, do they posses the cognitive abilities to undertake complex decisions in an uncertain world? These questions were addressed implicitly by John Muth in explaining expectational behaviour. In his famous pathbreaking article (1961), Muth observed that even though expectations play a very important role in shaping the behaviour of economic agents, no theory of expectation formation was developed that was consistent with empirical evidence and principles of economic theory.